Complete Genome Sequence of the Largest Known Flavi-Like Virus, Diaphorina citri flavi-like virus, a Novel Virus of the Asian Citrus Psyllid, Diaphorina citri - Matsumura, Emilyn E. [UNESP]; Nerva, Luca; Nigg, Jared C.; Falk, Bryce W.; Nouri, Shahideh (Amer Soc Microbiology, 2016)
A novel flavi-like virus tentatively named Diaphorina citri flavi-like virus (DcFLV) was identified in field populations of Diaphorina citri through small RNA and transcriptome sequencing followed by reverse transcription (RT)-PCR. We report here the complete nucleotide sequence and genome organization of DcFLV, the largest flavi-like virus identified to date.